Weed Control Measures and Moisture Conservation Practices Effects on Seedbank Composition and Vertical Distribution in the Soil - Girma Woldetsadik; Sombat Chinawong; Rungsit Suwanketnikom; Sunanta Juntakool; Visoot Verasan (Agriculture and Natural Resources, 2005)
Change in the weed seedbank due to crop production practices is an important determination of subsequent weed problems. Research was conducted to compare weed seed bank composition and vertical distribution of weed seed in the soil among four weed control measures and four moisture conservation practices at Dera Sub-Center and Melkassa Agricultural Research Center. Seed numbers at 45 cm depth were lower in pre-emergence of primagram at the rate of 3 L/ha treatment (137 seeds/m-2) and pre- and post-emergence of primagram at the rate of 3 L/ha plus 2, 4-D at the rate of 1 L/ha (105 seeds/m-2) at Dera and Melkassa, respectively. More than 60% of the weed seed bank was concentrated in the upper 15 cm of soil layer in post-emergence treatment at Dera and pre plus post-emergence at Melkassa site. The seed bank of the moisture conservation treatments was more uniformly distributed over depth and greater than the other systems. Chenopodium fasciulosum, Cyprus rotundus, Eragrostis aspera, and Sorghum arundenanceum were the most commonly found in the seed bank.